A Multiple Case Study of Sustainability Issues in Companies from Sugar and Ethanol Industrial Sector - Satolo, Eduardo Guilherme; Calarge, Felipe Araujo; Miguel, Paulo Augusto Cauchick (Brazilian Journal of Operations & Production Management, 2013)
The sugar cane and ethanol agricultural industrial sector has emerged as one of the most prominent industrial sectors in developing countries like Brazil. Sustainability issues are now more and more important and companies from this sector have been structured their operations to achieve positive results. One of the ways of doing that is by implementing an integrated quality and environmental management system. In this context, this paper aims at identifying the relevant practices related to integrated management systems in four organizations that belong to the sugar cane and ethanol industrial sector. Data were gathered through a questionnaire and semi-structured interviews. The paper highlights relevant issues in policy of the four units. An individual case description is made in addition to a cross-case comparison. As a result, an analysis of management systems in those units enables to raise important issues on how the studied companies take care of their environment economically and with their use for continuous improvement. Finally, the evidence shows a general concern for the environment although this is demonstrated by a culture of reducing residuals and the control of waste of natural resources.